Neurofascin (NF)155- and NF186-Specific T Cell Response in a Patient Developing a Central Pontocerebellar Demyelination after 10 Years of CIDP - Klehmet, Juliane; Staudt, Max; Diederich, Jan-Markus; Siebert, Eberhard; Meinl, Edgar; Harms, Lutz; Meisel, Andreas (Frontiers in Neurology, 2017)
Background: Information and pathobiological understanding about central demyelinating manifestation in patients, who primarily suffer from chronic demyelinating polyneuropathy (CIDP), are scarce. Methods: IFN-γ-response as well as antibodies against the (para)nodal antigens neurofascin (NF) 155 and NF 186 had been tested by Elispot assay and ELISA before clinical manifestation and at follow up. Case description and results: The patient described here developed a sub-acute brainstem syndrome more than ten years after diagnosis of CIDP under low-dose maintenance treatment of intravenous immunoglobulins (IVIG). MRI revealed enhancing right-sided pontocerebellar lesion. CSF examination showed mild pleocytosis and elevated protein, and negative oligoclonal bands. Further diagnostics exclude differential diagnoses such as tuberculoma, sarcoidosis or metastasis. Specific IFN-γ response against NF155 and NF186 as measured by Elispot assay was elevated before clinical manifestation. NF155 and NF186 antibodies were negative. Escalation of IVIG treatment at 2 g/kg BW followed by 1.4 g/kg BW led to clinical remission albeit to a new asymptomatic central lesion. Follow up NF155 and NF186- Elispot turned negative. Conclusion: The case reported here with a delayed central manifestation after an initially typical CIDP and NF155 and NF186 T cell responses does not resemble described cases of combined central and peripheral demyelination but may reflect a novel subtype within the great clinical heterogeneity of CIDP.